Natural convection and entropy production in a cubic cavity heated via pin-fins heat sinks - Al-Rashed, Abdullah A. A. A.; Kolsi, Lioua; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal; Borjini, Mohamed N. (Edizioni Ets, 2017)
In this study, heat transfer, flow structure and produced entropy due to natural convection in a three-dimensional cavity heated via heat sinks are investigated numerically. One wall of the cavity is heated via pin-fins and opposite wall is maintend at lower temperature. Remaining bouandaries are considered as adiabatic. Finite volume method is used to solve governing equations. Three geometrical cases are tested according to number and location of the fins. Other governing parameters are Rayleigh number and fin length. Number and length of the fins were found to be the most effective parameters on both heat transfer and entropy generation.
Keywords: Entropy Production; 3D Natural Convection; Heat Sinks; Flow Structure